Nutrition Education on Knowledge and Attitudes Regarding the Need for Vitamin A - Syafidawati, Fakhria; Noerfitri, Noerfitri (Universitas Padjadjaran, 2024)
Coverage of vitamin A capsules received by children aged 6-59 months in the last 12 months at the provincial level in 2018, 17.6% of children in Indonesia never received vitamin A capsules. Research regarding the need for vitamin A in school-aged children is important because there are concerns that low coverage of vitamin A capsules in toddlers can have a negative impact on the need for vitamin A in school-aged children. The method used in this research is an experimental with a research design, namely pre-experimental with one group pretest and posttest design with a total of 30 students as respondents. Then, this research aims to determine the effect of nutrition education through animated video media on the knowledge and attitudes of elementary school students regarding the need for vitamin A. In statistical analysis, the Wilcoxon test was carried out to evaluate knowledge with a p-value of 0.00005, and the paired T-test. The Dependent test is used to test attitudes with a p-value of 0.072. It can be concluded that school-age children's knowledge about the need for vitamin A increased significantly after they received nutrition education through animated videos, but there was no significant increase in their attitudes regarding the need for vitamin A. Keywords: Attitude, knowledge, nutrition education.